2017
DOI: 10.3390/e19110613
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Applications to Water Monitoring Network Design: A Review

Abstract: Abstract:Having reliable water monitoring networks is an essential component of water resources and environmental management. A standardized process for the design of water monitoring networks does not exist with the exception of the World Meteorological Organization (WMO) general guidelines about the minimum network density. While one of the major challenges in the design of optimal hydrometric networks has been establishing design objectives, information theory has been successfully adopted to network design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 70 publications
(138 reference statements)
0
25
0
Order By: Relevance
“…As second measure to evaluate the information loss when stations are removed from the network, we use a kriging based geostatistical approach (Adhikary et al, 2015;Keum et al, 2017). Kriging is an optimal surface interpolation technique assuming that the variance in a sample of observations depends on their distance (Adhikary et al, 2015).…”
Section: Relative Kriging Errormentioning
confidence: 99%
“…As second measure to evaluate the information loss when stations are removed from the network, we use a kriging based geostatistical approach (Adhikary et al, 2015;Keum et al, 2017). Kriging is an optimal surface interpolation technique assuming that the variance in a sample of observations depends on their distance (Adhikary et al, 2015).…”
Section: Relative Kriging Errormentioning
confidence: 99%
“…A successful environmental water quality monitoring program relies on the following main elements [26]; identification of the monitoring objectives, national and EU institutional setting, preliminary surveys, monitoring design (selection of representative sampling sites and frequencies, and water quality variables), adjustment to budget and operational restrictions, design of field protocols, field monitoring operations, laboratory activities, quality-assurance procedures, data management and analysis, and product development and reporting. Based on the review concerning the design of water quality monitoring networks, there is a variety of methodological approaches, e.g., statistical, multicriteria decision-making, entropy-based and fuzzy logic approaches, or a combination of the above (e.g., [27][28][29][30][31][32][33][34]). These methodologies are usually difficult to be applied by not qualified personnel and require long and reliable time-series [35]; therefore, they are usually used in evaluation and optimization of an existing monitoring program, rather than in the initial design of water quality monitoring network.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the examples include: water quality monitoring [7][8][9], water level monitoring [10], stream flow monitoring [11,12], fluid dynamic applications [13,14] and predicting the dynamic variations of a groundwater system [15]. Comprehensive reviews can be found in [16][17][18] for different water systems. Entropy theory developed by [19] is used for water quality monitoring networks optimization in rivers [7,20,21], in a bay [22], in sewer systems [23,24] and groundwater [25][26][27].…”
Section: Introductionmentioning
confidence: 99%